Evaluasi Pelaksanaan Literasi Membaca Dan Menulis Di SMP Bumi Makmur Di Kabupaten Musirawas Utara - Anggi (UNIVERSITAS BENGKULU, 2023)
The purpose of this study was to evaluate the literacy program for reading and writing at the Bumi Makmur Junior High School, North Musi Rawas Regency. The method in this study is the type of evaluation research. Data collection techniques are observation interviews and documentation. The data analysis technique used qualitative evaluation. The results of the study showed that in general it was running smoothly by making reading and writing habits in the reading corners of each class. The context aspect refers to the Permendikbud policy, the input aspect is that the principal, teachers and students have readiness to carry out reading and writing literacy, the process aspect is carried out in the morning literacy habituation 15 minutes before the learning process and the output is that students are more active and enthusiastic in taking lessons, accustomed to reading, write essays.